KUALITAS TEKWAN BERBAHAN DASAR JAMUR TIRAM PUTIH - Virginia Shaw; Anak Agung Ketut Alit Pujawan; Ngakan Putu Sudiarta (JURNAL GASTRONOMI INDONESIA, 2023)
This study aims to evaluate the sensory quality of food products using the organoleptic test method. This method was applied to evaluate the sensory quality of tekwan, a traditional Indonesian fish cake, made with substituted milkfish using white oyster mushroom. Organoleptic tests using a Likert scale were conducted with 20 panelists. Three levels of white oyster mushroom treatment were used, namely 0%, 25%, and 50%. The results showed that the use of white oyster mushroom could affect the sensory quality of tekwan. Panelists preferred tekwan without white oyster mushroom over those with 25% and 50% white oyster mushroom. However, there were significant differences in aroma and overall liking between tekwan with 0% and 25% white oyster mushroom. Therefore, the use of white oyster mushroom in tekwan production should be carefully considered to maintain the sensory quality of the product. This study provides information on the use of white oyster mushroom as an alternative ingredient in food product development and can serve as a reference for further research in this field.